Implementasi Program Sekolah Menulis dalam Mengasah Efikasi Diri Melalui Persuasi Verbal Santri di Pesantren Putri Walisongo Cukir Jombang - Fauzi, Azizah Asmaul; Kibtiyah, Asriana; Hanifudin, Hanifudin; Idawati, Khoirotul (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This study aims to describe the implementation of the writing school Program in honing the self-efficacy of students through verbal persuasion in Pondok Pesantren Putri Walisongo Cukir Jombang. This study uses a descriptive qualitative approach to the method of data collection through observation, interviews, and documentation. The results showed that this program effectively increases the confidence of students in writing. This is indicated by the increased self-efficacy of students after obtaining consistent verbal support from teachers and peers, as well as a supportive learning environment. The Program also facilitates the improvement of critical thinking skills, writing Systematics, and good use of language. However, there are obstacles such as limited facilities and infrastructure, lack of reference book collection, and lack of access to supporting technology. These findings emphasize the importance of the role of teachers and peers in providing constructive verbal persuasion to improve students ' self-efficacy, especially in writing skills.